The Influence of The Covid-19 Pandemic On The Food Sector – Various Aspects - Magdalena NIEWCZAS-DOBROWOLSKA; Tadeusz SIKORA (Communications of International Proceedings, 2021)
This paper presents various aspect of the influence of the COVID-19 pandemic on the food sector at each step of the food chain. Although the food industry has not been subject to very strict restrictions because of the essential good production, some changes took place. Farmers, food producers, food distributors, retailers and finaly consumers had to change their behaviour and attitudes. They all have the same goal that was the food safety as well as the human safety and avoidance of COVID-19 transmission. The first limitation that was most noticeable was the limitation in the number of people making purchases and also problems with the avaiability of goods. Due to the requirements of keeping distance, limitation of interractions between employees food producers had to reorganized their work. Moreover, irrespective of their function in the food chain, everyone has been associated with fear and insecurity
Keywords: Food; Food Industry; Consumer; COVID-19